Senna singueana: antioxidant, hepatoprotective, antiapoptotic properties and phytochemical profiling of a methanol bark extract - Sobeh, Mansour; Cheng, Haroan; Wink, Michael (Molecules, 2017)
Natural products are considered as an important source for the discovery of new drugs to treat aging-related degenerative diseases and liver injury. The present study profiled the chemical constituents of a methanol extract from Senna singueana bark using HPLC-PDA-ESI-MS/MS and 36 secondary metabolites were identified. Proanthocyanidins dominated the extract. Monomers, dimers, trimers of (epi)catechin, (epi)gallocatechin, (epi)guibourtinidol, (ent)cassiaflavan, and (epi)afzelechin represented the major constituents. The extract demonstrated notable antioxidant activities in vitro: In DPPH (EC50 of 20.8 µg/mL), FRAP (18.16 mM FeSO4/mg extract) assays, and total phenolic content amounted 474 mg gallic acid equivalent (GAE)/g extract determined with the Folin-Ciocalteu method. Also, in an in vivo model, the extract increased the survival rate of Caenorhabditis elegans worms pretreated with the pro-oxidant juglone from 43 to 64%, decreased intracellular ROS inside the wild-type nematodes by 47.90%, and induced nuclear translocation of the transcription factor DAF-16 in the transgenic strain TJ356. Additionally, the extract showed a remarkable hepatoprotective activity against d-galactosamine (d-GalN) induced hepatic injury in rats. It significantly reduced elevated AST (aspartate aminotransferase), and total bilirubin. Moreover, the extract induced a strong cytoplasmic Bcl-2 expression indicating suppression of apoptosis. In conclusion, the bark extract of S. sengueana represents an interesting candidate for further research in antioxidants and liver protection.